Emotional and behavioral problems in infants and preschool children: prevalence and sociodemographic risk factors - Uğur, Çağatay; Yürümez, Esra; Yılmazer, Yasemin (The European Research Journal, 2019)
Objectives: To determine the prevalence of behavioral disorders and the relationship between sociodemographic, environmental and family factors among infants and preschool children applied to psychiatry clinic. Methods: The sample comprised 355 children between 20-59 months of age and showing normal developmental pattern. After psychiatric assessments, the patients were referred to the child development unit for developmental assessment, support and psychoeducation. Ankara Developmental Screening Inventory (ADSI) was applied to all participants. Results: The mean age was significantly higher among the children applied to the clinic due to limit setting problems (LSP) than that of the children applied due to the other problems. The children with speech delay were the group applied to the clinic at the earliest age. Speech delay rates were higher among boys compared with girls. Sibling jealousy was more common among girls than boys. In the group with LSP, fathers’ education levels were lower than that of the group without LSP. There was no difference between children in terms of the number of siblings, birth order and family size. Conclusion: The findings indicate that limit setting was by far the most common problem among children applied to our clinic. Consequently, the utility of results to raise intervention strategies within limit setting should be developed and intervened earlier.